The Experiences of Emergency Nurses During the Covid-19 Crisis: Factor Analysis - Ahmed Atallah AlQurash; Abdulellah Al Thobaity; Modi Owied Al Moteri; Mohammed Almalki; Waleed Ali AlAhmari (Health Notions, 2020)
Emergency nurses are in the frontline in managing COVID-19 crises. Directly encountering and dealing with infected patients put nurses at high risk. To date, evidence about emergency nurses’ experiences of COVID-19, particularly those in the frontline, are limited. Understanding the experience and impact of the COVID-19 crisis on emergency nurses could contribute to improving nursing and disaster practices. This study aimed to explore the experiences of emergency nurses during their responses to the COVID-19 crisis. Thus, A cross-sectional design was used. For the data collection, a questionnaire was constructed and its validity and reliability was rigorously evaluated by principle component analysis (PCA), exploratory factor analysis (EFA), and confirmatory factor analysis (CFA). The data were collected in two phases, in which 111 and 128 emergency nurses were recruited from different hospitals in Saudi Arabia. The primary purpose of PCA; EFA and CFA to delete weak loading and extract and confirm factors. The findings of using factor analysis, of the 22 items, 11 items were retained with strong factor loadings (0.88 to 0.54) to three factors. The three factors were worry (4 items), compliance (4 items), and cautiousness (3 items). The reliability of the three factors was 0.84, 0.86, and 0.73, respectively, indicating that the scale had good reliability. The 11 scale items had robust psychometric properties, which implies that they could be used to evaluate emergency nurses’ experience in encountering and dealing with the COVID-19 crisis. Although nurses in the frontline showed compliance with infection control prevention measures, they were likely to experience certain degrees of fear and worry, which could lead to burnout. Hence, it is highly recommended to help nurses overcome such crises by providing consistent support and reassurance. Keywords: mmergency nursing; COVID-19; crisis; nursing care and experiences